2016
DOI: 10.1016/j.resp.2016.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Baroreceptor reflex during forced expiratory maneuvers in individuals with chronic spinal cord injury

Abstract: Pulmonary and cardiovascular dysfunctions are leading causes of morbidity and mortality in patients with chronic Spinal Cord Injury (SCI). Impaired respiratory motor function and decreased Baroreflex Sensitivity (BS) are predictors for the development of cardiopulmonary disease. This observational case-controlled clinical study was undertaken to investigate if respiratory motor control deficits in individuals with SCI affect their ability to perform the Valsalva maneuver, and to determine if a sustained Maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…Previous studies have indeed shown that mainly patients with high-cervical motor-complete SCI are also less capable to sufficiently perform the Valsalva maneuver. 40 Therefore, our findings support the concept that CSFP response during Queckenstedt’s test is due to a relative intracranial volume change, whereas the Valsalva maneuver is mainly related to intrathoracic and intraabdominal pressure changes, associated with an increased intracranial venous filling, but also with a reverse flow to the spinal venous plexus.…”
Section: Discussionsupporting
confidence: 85%
“…Previous studies have indeed shown that mainly patients with high-cervical motor-complete SCI are also less capable to sufficiently perform the Valsalva maneuver. 40 Therefore, our findings support the concept that CSFP response during Queckenstedt’s test is due to a relative intracranial volume change, whereas the Valsalva maneuver is mainly related to intrathoracic and intraabdominal pressure changes, associated with an increased intracranial venous filling, but also with a reverse flow to the spinal venous plexus.…”
Section: Discussionsupporting
confidence: 85%
“…Participants were assessed in a seated position, without the aid of compression garments or abdominal binders 43, 44 . To assess BS, participants blew with maximal effort into a mouthpiece for the duration of an audible, 5s tone (5s MEP) 45 . Each event was attempted three times, with at least 30s rest in between events to allow BP values to return to baseline.…”
Section: Methodsmentioning
confidence: 99%
“…The slope of each phase is reported in ms/mmHg, which quantifies the change in RRI for every 1 mmHg increase or decrease of SBP 46–48 . Acceptable attempts were those between 5 and 7s in duration 49, 50 with a Pearson correlation coefficient > .80 47, 51, 52 ; BS outcomes were excluded if the maneuver did not meet 27 cmH 2 O 45 , or if they triggered spasms, autonomic dysreflexia, or coughs. The phases analyzed began with three consecutively increasing or decreasing RRIs 47, 52 ; the mean of all acceptable attempts was used for statistical analysis.…”
Section: Methodsmentioning
confidence: 99%
“…However, we recently demonstrated a modification of the Valsalva maneuver that affords individuals with high cord injury the ability to adequately perform the maneuver in the presence of respiratory muscle weakness. 73…”
Section: Evaluation and Consequences Clinical Evaluationmentioning
confidence: 99%